2021
DOI: 10.1186/s12957-021-02147-z
|View full text |Cite
|
Sign up to set email alerts
|

High GFPT1 expression predicts unfavorable outcomes in patients with resectable pancreatic ductal adenocarcinoma

Abstract: Background Glutamine-fructose-6-phosphate transaminase 1 (GFPT1) is the first rate-limiting enzyme of the hexosamine biosynthesis pathway (HBP), which plays a pivotal role in the progression of pancreatic ductal adenocarcinoma (PDAC). Therefore, we investigated the prognostic significance of GFPT1 expression in patients with resectable PDAC. Methods We analyzed public datasets to compare GFPT1 expression in tumor tissues and normal/adjacent pancrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Emerging evidence has revealed that amino acid metabolism plays an important role in PC initiation and progression (31)(32)(33). Consistent with former studies, several amino acid transporters were also found to be highly expressed in PC tumor tissues to satisfy the increased need for proliferation (Figure 3B), such as cytoplasmic aspartate transaminase (GOT1) (34), proline oxidase (PRODH1) (35), and glutamine fructose 6-phosphate amidotransferase-1 (GFPT1) (36)(37)(38).…”
Section: Discussionsupporting
confidence: 78%
“…Emerging evidence has revealed that amino acid metabolism plays an important role in PC initiation and progression (31)(32)(33). Consistent with former studies, several amino acid transporters were also found to be highly expressed in PC tumor tissues to satisfy the increased need for proliferation (Figure 3B), such as cytoplasmic aspartate transaminase (GOT1) (34), proline oxidase (PRODH1) (35), and glutamine fructose 6-phosphate amidotransferase-1 (GFPT1) (36)(37)(38).…”
Section: Discussionsupporting
confidence: 78%
“…The prognosis of patients with pancreatic cancer is very poo r[ 41 , 42 ]. The NEJM [ 43 ] and other magazines have reported that the monoclonal antibody drug blocking immunoassay (such as PD-1 and PD-L1) is effective for treating non-small cell lung cancer, malignant melanoma, renal cell carcinoma, ovarian cancer, stomach cancer, and breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The hsa_circ_0055054 is formed through the cyclization of exons 10–11 of the glucosamine-fructose-6-phosphate aminotransferase isomerizing 1 (GFPT1) gene. Previous studies have reported that GFPT1 may contribute to the progression of cervical ( 43 ), pancreatic ( 44 ) and esophageal cancer ( 45 ), but the function of hsa_circ_0055054 remains unknown. The present study demonstrated that the expression of hsa_circ_0055054 was significantly higher in HCC tissues compared with the corresponding adjacent normal tissues, and that it binds to miR-122-5p.…”
Section: Discussionmentioning
confidence: 99%